ANALYSIS OF HYDROCARBONS IN ALGERIA’S APPROACH TO BRICS MEMBERSHIP 2024 - Anisa Nurul fitria Sholihah; Gloria Esmeralda Oliveira; Diah Ayu Puspitasari; Septyanto Galan Prakoso (Pena Wimaya, 2025)
Algeria's hydrocarbon sector dominates more than 90% of the country’s income as the second largest GDP in North Africa. Algeria is one of the countries with the largest natural gas and oil reserves in the world. Today, most of Algeria's hydrocarbon resources come from old mines because about two-thirds of Algeria's territory has not been explored. Although hydrocarbon resources are non-renewable energy, research estimates that more than 100 discoveries in Algeria can still be developed. Algeria recently has a desire to join the political and economic cooperation group of developing countries rich in natural resources, including Brazil, Russia, India, China and South Africa (BRICS). Currently BRICS covers 40% of the world's population and contributes to around 28% of total world GDP. This article aims to look at the power of the hydrocarbon sector as Algeria begins its economic relations with organizations such as BRICS using the Theory of Complex Interdependence by Robert Keohane and Joseph Nye, and the Bandwagoning Concept by Kenneth Waltz.